2021
DOI: 10.1111/cdev.13521
|View full text |Cite
|
Sign up to set email alerts
|

More Later: Delay of Gratification and Thought About the Future in Children

Abstract: We investigated whether individual differences in future time perception and the detail with which future events are imagined are related to children’s delay of gratification. We administered a delay choice task (real rewards), a delay discounting task (hypothetical rewards), a novel future time perception measure, an episodic future thinking (EFT) interview and IQ measures to a sample of 7‐ to 11‐year‐olds (N = 132) drawn from a urban predominately white population in N. Ireland. We found a strong correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 71 publications
4
7
0
1
Order By: Relevance
“…Relatedly, we can ask more directly about the contribution of imagination to the development of new social knowledge in children, and the consequences of new ideas on the breadth of interpretations that children consider. Rather than exploiting children's imaginations for methodological purposes only—telling them fictional stories to find out what they know—we can encourage them to tell us stories, and ask how their imaginations change what they know (Burns, O'Connor, et al, 2021; Chernyak et al, 2017; Gaither et al, 2020). Another promising avenue of research is the link between action experience, causal knowledge, and social meaning‐making.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, we can ask more directly about the contribution of imagination to the development of new social knowledge in children, and the consequences of new ideas on the breadth of interpretations that children consider. Rather than exploiting children's imaginations for methodological purposes only—telling them fictional stories to find out what they know—we can encourage them to tell us stories, and ask how their imaginations change what they know (Burns, O'Connor, et al, 2021; Chernyak et al, 2017; Gaither et al, 2020). Another promising avenue of research is the link between action experience, causal knowledge, and social meaning‐making.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies found that individual differences in EFT are associated with differences in discounting in adolescents ( Bromberg et al, 2015 ; McCue et al, 2019 ). Burns et al (2021) found a weak correlation between EFT ability and performance on delay discounting in children aged 7–11 years, but the correlation did not survive after controlling for age and IQ. These inconsistent findings may be because the EFT ability itself continues to develop from childhood to adolescence, and children require more effort to engage in EFT than adolescents.…”
Section: Introductionmentioning
confidence: 89%
“…To control for the possible effect of fluid intelligence on the relation between EFT and delay discounting ( Shamosh and Gray, 2008 ; Nusbaum and Silvia, 2011 ; Burns et al, 2021 ; Frith et al, 2021 ), we assessed the participants’ fluid intelligence using the Raven’s Standard Progressive Matrices for adults ( Raven and Court, 1998 ), which is a global nonverbal measure of abstract reasoning and has been proven to have good reliability and validity in Chinese sample ( Zhang, 1989 ). It consists of 60 items, in which participants were shown a matrix of pictures with missing parts and asked to select one of several possible answers that matches the visual features of the pictures.…”
Section: Methodsmentioning
confidence: 99%
“…Not only does the ability to choose to delay gratification improve over the preschool period (see Garon, 2016, for review), developmental improvements are also observed on delay discounting tasks across childhood and over the adolescent period (Green, Fry, & Myerson, 1994;Steinberg et al, 2009), although, as in adults, there are also substantial individual differences in child and adolescent populations (e.g., Burns, O'Connor, Atance, & McCormack, 2021;Khurana, Romer, Betancourt, & Hurt, 2018). Given children's welldocumented difficulties with delaying gratification, an intervention that promotes patient decision making in this population may have valuable applications.…”
Section: Adolescents and Adultsmentioning
confidence: 99%